Deficits and opportunities, pivots and shifts for scaling-up voluntary medical male circumcision in Uganda: a qualitative reflexive thematic analysis study - John Bekiita Byabagambi; Bruce Hollingsworth; Mark Limmer (BMC, 2024)
Abstract Despite voluntary medical male circumcision (VMMC) being a cost-effective intervention for preventing HIV transmission, its scale-up has faced challenges. Several interventions to address these challenges in priority countries, including Uganda, have not yielded the desired results. This cross-sectional qualitative study aimed to explore the factors that affect the demand for VMMC and identify possible solutions. Semi-structured phone interviews were conducted with 29 males aged at least 18 and not more than 65 drawn randomly from a database representative of the general population maintained by an independent research organisation. Reflexive thematic analysis was conducted, and data analysis was done using NVivo version 12. The results were presented in narrative format with supporting quotes. The study received ethical and regulatory clearance to be conducted in Uganda. The average age of the respondents was 28 years. Almost all respondents had some education, and most lived in rural areas. Two themes were generated, namely, 1) deficits and opportunities for VMMC, which are issues that currently hinder the uptake of VMMC but, if addressed, would lead to better demand, and 2) pivots and shifts for VMMC, which are changes that need to be made to improve the uptake of VMMC. We found that several challenges, including myths, misconceptions, health system gaps, and uncertainties about the postoperative period, hindered the uptake of VMMC. Pivots and shifts for improving the uptake of VMMC include intensifying VMMC campaigns, addressing inequities, and addressing access barriers. We concluded that several challenges, including myths and misconceptions, health system-related gaps, and uncertainties in the post-circumcision period, persist and negatively impact the scale-up of VMMC in Uganda. VMMC beneficiaries have plausible proposals for addressing challenges. The Uganda Ministry of Health should address the myths, misconceptions, health system-related gaps, and uncertainties about the postoperative period and should involve VMMC beneficiaries in reviewing interventions to address gaps.